Perlawanan Masyarakat Desa dan Pemerintah Kabupaten dalam Rencana Tambang Emas Trenggalek - Wibowo, Prastu Heri (Paradigma, 2023)
The gold mining industry is an alternative to economic development that the government is offer to its society especially in developing countries. In practice, the gold mining plan in Trenggalek has created forms of resistance from society that do not want a mine. This study aims to identify the gold mine plan and analyze the forms and causes of resistance from the village society and the district government. This study uses the dependency theory of Andre Gunder Frank and James C. Scott to analyze the forms and causes of resistance. The research uses the case study method of Robert K. Yin. The research location is in the area affected by the PT SMN gold mining concession plan in Trenggalek Regency. The results showed that the Trenggalek gold mine plan was carried out by PT Sumber Mineral Nusantara which is affiliated with Far East Gold from Australia through the Mining-Production Operations License (IUP-OP) issued by the East Java Provincial Government accompanied by the roles of the local bourgeoisie who tried to launch the gold mine plan to be realized in Trenggalek Regency. The forms of open resistance carried out by the village society were demonstrations, online petitions, and tearing up the company’s application letter. Meanwhile, the form of open resistance from the district government is the publication of attitudes to the media, signing a rejection petition, and submitting a letter of review. The symbolic forms of closed resistance by the village society are tree planting, mining t-shirts, and environmental journalism as well as daily closed resistance including discussions on environmental education and religious activities in the form of yasinan. Meanwhile, the closed resistance from the district government includes delaying the ratification of the spatial planning and territory (RTRW) and cooperating with parties capable of negating mining plans, namely the agency that has the authority to protect karst. The cause of the resistance was state domination through the issuance of IUP-OP to PT SMN as the initiator of the gold mine plan in Trenggalek Regency which led to the sub-dominance of resistance, namely material, status, and ideology.